Dibalik Target Produksi: Eksplorasi Kompetensi Kerja dan Tantangan Kinerja Karyawan - Fhiresti Duha; Ray Octafian (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore work competencies and identify employee performance challenges in achieving production targets at PT. Woori Sukses Apparel Semarang. The competitive garment industry requires employees to possess adequate competencies in order to meet the production targets set by the company. However, various internal and external challenges often become obstacles to achieving optimal performance. This study uses a qualitative approach with a case study method to gain an in-depth understanding of the phenomenon being studied. Data collection was conducted through in-depth interviews with employees from various levels, direct observation of work processes, and analysis of company documents. The research informants consisted of supervisors, production operators, quality control personnel, and administrative staff selected through purposive sampling. Data were analyzed using thematic analysis techniques to identify patterns and themes that emerged from the collected data. The results of the study show that employee competencies at PT. Woori Sukses Apparel Semarang include technical competencies such as operating sewing machines, mastering sewing techniques, and understanding product quality standards. Non-technical competencies include communication skills, teamwork, and adaptability to changing production targets. Performance challenges faced by employees include time pressure to meet daily targets, limited skills in handling complex product models, lack of continuous training, and work environment conditions that affect productivity. The study also reveals a gap between the competencies possessed by employees and the increasingly complex job demands. Factors such as time management, work motivation, and organizational support role in determining the success of achieving production targets.